A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 3 years ago
6.03] If you wanted to eliminate the y variable by adding the two equations in the following system, what could be your first step?
3x + y = 6
4x − 5y = 10
Multiply the first equation by 5.
Multiply the first equation by −5.
Multiply the first equation by −4.
Add the two equations together.
Question 5 (Multiple Choice Worth 4 points)
[6.02] For the following system, if you isolated x in the second equation to use the Substitution Method, what expression would you substitute into the first equation?
3x + y = 8
−x − y = −7
−y + 7
−y − 7
y + 7
y − 7
anonymous
 3 years ago
6.03] If you wanted to eliminate the y variable by adding the two equations in the following system, what could be your first step? 3x + y = 6 4x − 5y = 10 Multiply the first equation by 5. Multiply the first equation by −5. Multiply the first equation by −4. Add the two equations together. Question 5 (Multiple Choice Worth 4 points) [6.02] For the following system, if you isolated x in the second equation to use the Substitution Method, what expression would you substitute into the first equation? 3x + y = 8 −x − y = −7 −y + 7 −y − 7 y + 7 y − 7

This Question is Open

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.06.03) You would multiply the first equation by 5. This is because: (1) 3x + y = 6 (Multiply by 5 = (2) ) + 4x − 5y = 10 (2) 15x +5y = 30 + 4x  5y = 10 (add x's, y's and 30 + 40 = (3) ) (3) 19x +0y = 40 (times y by 0 = (4) ) (4) 19x =40

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0[6.02] y +7 This is because: (1) −x − y = −7 (leave x on its own and move y to the other side to get (2) ) (2) x = 7 + y (multply (7+y) by negative () to get (3) ) (3) x = 7  y (switch 7 and y around to get the answer that is required in choices (4) ) (4) x = y + 7 (answer)

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0The answer would be A) Multiply the first equation by 5. because (3x + y = 6)5 4x − 5y = 10 15x + 5y = 30 + 4x  5y = 10 19x = 40 (19x)/19 = (10)/19 x\[\approx0.53\]

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0thank you and whats the foil method?? and how would you apply it
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.